Evaluating preschool linear growth velocities: an interim reference illustrated in Nepal - Manohar, Swetha; Colantuoni, Elizabeth; Thorne-Lyman, Andrew Lucian; Shrestha, Binod; Adhikari, Ramesh Kant; KC, Angela; Bhattarai, Abhigyna; West Jr., Keith Parker (Cambridge University Press, 2023)
Objective: An annualised linear growth velocity (LGV) reference can identify groups of children at risk of growing poorly. As a single velocity reference for all preschool ages does not exist, we present an interim tool, derived from published, normative growth studies, for detecting growth faltering, illustrating its use in Nepali preschoolers.